Law aspects of individual and group nurse practice - Urbaniak, Monika; Zdanowska, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
The principle of economic activity freedom expressed in the article 22 of the Constitution of the Republic of Poland gives the nurses the chance to choose an organizational form to perform their profession. They can work on the basis of an employment contract in public or non public health care institutions or besides those institutions or on the basis of the civil contract to provide healthcare service inside or outside health care center. The nurses can also work on the basis of an individual practice, a specialistic practice, and a group practice. Than they become enterpreneurs as expressed on the 2nd July 2004 act on economic activity freedom, associates in a civil company or in a partnership company. Their activity as a private practice is regulated, meaning the necessity to register it in the individual practice, specialistic practice or group practice held by proper board of a district nurses and midwives association. Nursing Topics 2010; 18 (3): 358-362